Korfball Coach Training in Klaten Regency, Central Java - Lestari, Bhekti; Kharis Fajar, Muhammad; Ferdita Yuhantini, Eva; Resti Nurpratiwi; Rusdiawan, Afif; Muhammad Sidik, Rizky; Wiriawan, Oce; Ariyanto, Budi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service activity for training korfball coaches in Klaten Regency, Central Java aims to provide an understanding of training methods and an understanding of preparing training programs so that coaches can form and produce korfball athletes who excel in regional, national and even international championships. The method applied used a socialization approach with a training program followed by 50 participants consisting of teachers and football coaches in Central Java. The activity was held at KONI Klaten Regency for two days. The materials used in this activity are power points, teaching materials and videos as well as using laptops, projectors, mics and sound, stationery, documentation tools, korf and koftball balls. The first socialization material explains basic techniques, methods of training koftball and rules for playing koftball games. The second material discusses guidelines for preparing a simple exercise program. The third material discusses the importance of physiotherapy in the sport of korfball. Then the fourth material concerns physical training methods, techniques and tactics in korfball. The final material is about sports management in improving performance. After delivering all the material, it was continued with a korfball game simulation. The output of this activity is improving the quality of human resources for korfball coaches in Central Java.